Solubility determination and thermodynamic properties calculation of macitentan in mixtures of ethyl acetate and alcohols. (May 2021) - Li, Rongrong; Jin, Yanxian; Yu, Binbin; Xu, Qianqian; Chen, Xianlang; Han, Deman
Graphical abstract: Highlights: Study the solubility of macitentan (form I) in three mixed solvents; The solubility data were correlated by some thermodynamic models; Statistical analysis of calculation results; Some thermodynamic properties of dissolution process were evaluated. Abstract: Due to macitentan (form I) is hydrophobic and has poor solubility, in this work, the solubility of macitentan in (methanol + ethyl acetate), (ethanol + ethyl acetate) and (isopropanol + ethyl acetate) was studied and correlated. In three mixed solvents, the solubility increased with the increase of temperature. In pure solvents, the largest mole solubility data was in ethyl acetate (1.223 × 10 −2 at 313.15 K), followed by methanol (6.02 × 10 −4 at 313.15 K), ethanol (4.58 × 10 −4 at 313.15 K) and isopropanol (2.46 × 10 −4 at 313.15 K). The solubility increased monotonically with the increase of ethyl acetate mass fraction at all studied temperatures. In mixtures of (ethyl acetate + methanol), the values varied from 6.02 × 10 −4 to 1.223 × 10 −2 at 313.15 K, an increase of 20.32 folds, meanwhile, 26.70 folds for mixtures of (ethanol + ethyl acetate) and 49.72 folds for mixtures of (isopropanol + ethyl acetate). The values of relative average deviations ( RAD ) in three systems with Jouyban-Acree model are 6.20%, 5.95% and 4.95%, respectively. For CNIBS/R-K model, the data is less than 5.0% at the temperature range from 273.15 K to 293.15 K only in mixture of (ethyl acetate + methanol). However, the data of Residual Sum of Squares (RSS) for Jouyban-Acree model and CNIBS/R-K model are 5.72 and 2.26, respectively. According to the result of analysis, the CNIBS/R-K model could provide a suitable prediction in three mixed solvents. In the following, the analysis of apparent thermodynamic properties for the dissolution processes indicate the dissolution process is not only endothermic but also entropy-driving.